Semi-Global State Synchronization for Multi-Agent Systems Subject to Actuator Saturation and Unknown Nonuniform Input Delay - Zhang, Meirong; Saberi, Ali; A. Stoorvogel, Anton (IEEE transactions on network science and engineering, 2021)
The agent dynamics in a multi-agent system subject to both actuator saturation and unknown nonuniform input delay impose difficulty in the protocol design for all agents achieving state synchronization, although solutions can be found for agents with actuator saturation and for agents with input delay. In this paper, we design a low-gain based protocol for each agent such that the protocol output (agents' inputs) can be squeezed enough and the saturation is not activated. Moreover, an upper bound of the input delay is obtained. This paper focuses on a class of agent systems, i.e. all agents' eigenvalues are in the closed left half plane (that is at most unstable agents), and topology describing the coupling among agents is undirected, but weighed. The numerical results with six agents coupled with full states and partial states illustrates the effectiveness of the proposed protocol design.